Study of Survival of COVID19 Patients with Severe or Critical Symptoms: Study of D-dimer on Survival of COVID19 Patients with Severe or Critical Degrees in ICU COVID, Academic Hospital, Gadjah Mada University, Yogyakarta - Purwadi Sujalmo; Rosita Yunanda Purwanto; Rochmi Isnaini Rismawanti; Yanasta Yudo Pratama; Wandira Lalitya; Afridhia Bidari Fachrudin (Rumah Sakit Akademik Universitas Gadjah Mada, 2022)
The SARS-CoV 2 virus pandemic has been a scourge since 2020. The number of cases that continues to increase, both mild, moderate, severe-critical confirmed cases are directly proportional to the need for treatment rooms, both ordinary wards and intensive care units (ICU), which is inversely proportional to the available capacity. room. Based on research, the high mortality and morbidity rate due to COVID 19 is due to the incidence of patient sepsis. Research abroad states that the value of D-dimer is a prognostic factor for COVID-19 patients, although there is no agreement on the best cut-off point for specificity and sensitivity. hypercoagulability conditions and increased lactic acid in patients with severe sepsis. It is necessary to evaluate the role of this laboratory result in estimating the prognosis of COVID-19 patients in Indonesia. There is no study that examines the relationship between the incidence of sepsis and the characteristics of hypercoagulability with the dominance of the thrombotic process in COVID19 patients in Indonesia. The purpose of this study was to provide information to health workers about the role of D-dimer value as a prognostic factor for severe-critical COVID-19 patients. This quantitative retrospective research data in the form of proportions were collected for 12 months from the medical records of the UGM Academic Hospital of patients with confirmed severe-critical COVID-19. Overall survival was assessed by the Kaplan-Meier curve. The cut-off determination for the D-dimer variable was carried out using the Receiver Operating Curve (ROC) followed by the calculation of the Youden index. Then the hazard ratio was determined by cox regression with a p value of <0.05 which was considered significant. Statistical analysis with SPSS version 26 software.